2009
DOI: 10.1093/ndt/gfn712
|View full text |Cite
|
Sign up to set email alerts
|

CD2AP mutations are associated with sporadic nephrotic syndrome and focal segmental glomerulosclerosis (FSGS)

Abstract: Our findings suggest that CD2AP mutations modify the interaction with CD2 in lymphocytes and alter the composition of the renal slit diaphragm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
85
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 17 publications
3
85
2
1
Order By: Relevance
“…However, SH3-3 is unique in being linked to a disease-associated mutation; a polymorphism (K301M) in SH3-3 may play a role in hereditary focal segmental glomerulosclerosis (5). Lys-301 lies outside of the canonical binding groove and so would not be expected to interfere directly with peptide ligand docking, raising questions as to its exact role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, SH3-3 is unique in being linked to a disease-associated mutation; a polymorphism (K301M) in SH3-3 may play a role in hereditary focal segmental glomerulosclerosis (5). Lys-301 lies outside of the canonical binding groove and so would not be expected to interfere directly with peptide ligand docking, raising questions as to its exact role.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous CD2AP Ϫ/Ϫ mice develop progressive glomerular malfunction caused by the loss of podocyte foot process integrity and die of renal failure within 6 -7 weeks (3). Mutations identified in CD2AP (single nucleotide polymorphisms or deletions leading to protein sequence changes) result in abnormal kidney function and proteinuria with nephrotic syndrome caused by focal segmental glomerulosclerosis (4,5).…”
mentioning
confidence: 99%
“…However, the incidence of CD2AP and TRCP6 in our database of 400 cases of INS is less than 2%. 36,37 The development of next-generation techniques for molecular analysis will enable a more comprehensive analysis of all genes potentially involved in INS and characterization of patient populations in whom new therapies may be successful. Our study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genetic studies identified podocin, encoded by NPHS2, as a mutant gene that causes autosomal recessive steroid-resistant nephritic syndrome [3,29]. Likewise, CD2-associated protein (CD2AP) mutations are associated with sporadic nephrotic syndrome and focal and segmental glomerulosclerosis [11,32]. These genomic studies lead to the determination of a molecular topology for SD, required for maintaining the homeostasis of podocytespodocytes [21].…”
mentioning
confidence: 99%